Impact of Having Family History of Psoriasis or Psoriatic Arthritis on Psoriatic Disease - (:unkn) unknown (WILEY, 2020)
Objective Psoriatic arthritis (PsA) has a genetic background. Approximately 40% of patients with psoriasis or PsA have a family history of psoriasis or PsA, which may affect disease features. The aim of this study was to assess the effects of family history of psoriasis and PsA on disease phenotypes. Methods Data from 1,393 patients recruited in the longitudinal, multicenter Psoriatic Arthritis International Database were analyzed. The effects of family history of psoriasis and/or PsA on characteristics of psoriasis and PsA were investigated using logistic regression. Results A total of 444 patients (31.9%) had a family history of psoriasis and/or PsA. These patients were more frequently women, had earlier onset of psoriasis, more frequent nail disease, enthesitis, and deformities, and less frequently achieved minimal disease activity. Among 444 patients, 335 only had psoriasis in their family, 74 had PsA, and 35 patients were not certain about having PsA and psoriasis in their family, so they were excluded from further analysis. In the multivariate analysis, family history of psoriasis was associated with younger age at onset of psoriasis (odds ratio [OR] 0.976) and presence of enthesitis (OR 1.931), whereas family history of PsA was associated with lower risk of plaque psoriasis (OR 0.417) and higher risk of deformities (OR 2.557). Family history of PsA versus psoriasis showed increased risk of deformities (OR 2.143) and lower risk of plaque psoriasis (OR 0.324). Conclusion Family history of psoriasis and PsA impacts skin phenotypes, musculoskeletal features, and disease severity. The link between family history of psoriasis/PsA and pustular/plaque phenotypes may point to a different genetic background and pathogenic mechanisms in these subsets.